Biodegradable uniform microspheres based on solid-in-oil-in-water emulsion for drug delivery: A comparison of homogenization and fluidic device. (September 2014) - Ryu, Tae-Kyung; Kim, Sung Eun; Kim, Joo-Hwan; Moon, Seung-Kwan; Choi, Sung-Wook
Based on solid-in-oil-in-water emulsification, we fabricated biodegradable poly(ϵ-caprolactone) microspheres containing gentamicin using conventional homogenization and a fluidic device. The feasibility of the poly(ϵ-caprolactone) microspheres as drug carriers was evaluated in terms of encapsulation efficiency, release behavior of gentamicin, and antimicrobial activity. The poly(ϵ-caprolactone) microspheres prepared using a fluidic device (fluidic device microspheres) had a uniform diameter and a smooth surface, whereas the poly(ϵ-caprolactone) microspheres prepared using conventional homogenization (conventional homogenization microspheres) exhibited polydisperse and a porous structure. At 0.3 wt% of gentamicin concentration, the encapsulation efficiencies of the conventional homogenization and fluidic device microspheres were 39.5% and 72.0%, respectively. In addition, a significant amount of gentamicin was only released initially from the conventional homogenization microspheres, whereas the fluidic device microspheres released gentamicin in a sustained manner for 28 days. These results confirmed the superior performances of the uniform fluidic device microspheres for drug delivery system. We further proposed a model for microsphere formation to explain the difference in performance of the conventional homogenization and fluidic device microspheres.